AN ONLINE COMMUNITY SERVICE ACTIVITY FOR SHARING KNOWLEDGE ON WORK PATTERN ADAPTATION TRENDS - Christian, Michael; Wibowo, Suryo; Yuniarto, Yustinus (Universitas Bunda Mulia, 2022)
The protracted COVID-19 pandemic has had an impact on many aspects of people's lives. One of the most noticeable effects is in the business world, where the adaptation of new work patterns and behavior follows government policies, where non-essential offices are encouraged to use the work from home method. This activity, in the form of community service (PKM) via an online webinar using Zoom media, aims to provide information, education, and knowledge to the larger community. Organizational management must invariably quickly and precisely adapt work methods that can be accepted and carried out by employees. On the one hand, this method of working from home has made it possible for workers to work remotely and to do more than one job, or to do multitasking jobs. On the other hand, this method of working from home is consistently proving to be unsuitable for this type of work. In practice, this activity is divided into three sessions: a theoretical presentation of the concept of work behavior by the first speaker; an explanation of adaptation trends and work patterns during a pandemic from scientific publications by the second speaker; and an explanation of how to find trends in novelty and work adaptation by the third speaker. Third-party presenters use dimensions, bibliometrics, and VOSviewer. In addition to the presenters' good mastery of the material, the participants thought the materials and activities provided had good elements of accountability, objectivity, and transparency. Furthermore, the participants thought the material presented to them was of high quality